PROBLEMS AND SOLUTIONS IN THE STRUCTURE OF A TEACHER'S WORK (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Pedagogical activity is of primary importance in the development of society, and the main activity of today's teachers has become dependent on the means and methods of information technology. Therefore, a number of problematic tasks and obstacles are emerging before teachers. Pedagogical skills are being improved at the heart of teachers' pedagogical activities.